THE STANDARD INPATIENT CLASS (KRIS) POLICY IN HOSPITALS AND ITS IMPACT ON THE DECLINE IN BED AVAILABILITY FOR BPJS - Meidiawaty, Fusia (Ridwan Institute, 2024)
The Standard Inpatient Class (KRIS) policy introduced by BPJS Kesehatan aims to enhance equitable healthcare quality by standardizing hospital inpatient facilities in Indonesia. However, its implementation has raised concerns due to its significant impact on hospital bed availability, particularly in facilities with limited capacity, leading to challenges in service accessibility and quality. This study aims to examine the implications of the KRIS policy on bed capacity and healthcare service standards, as well as the obstacles faced by hospitals in maintaining service quality for BPJS participants. Employing a normative juridical method, the research systematically analyzes legal materials, including Presidential Regulation Number 59 of 2024, alongside relevant secondary literature. The findings reveal that the policy, while intended to improve service equity, has resulted in a notable decline in bed capacity, increased waiting times, and heightened workloads for medical personnel, particularly in resource-constrained hospitals. Hospitals in remote areas face additional challenges in meeting infrastructure requirements due to budget limitations. The study concludes that balancing the policy's quality standards with resource availability remains a critical issue, necessitating sustainable financial strategies, capacity-building programs, and innovative resource management solutions to ensure equitable healthcare access for all BPJS participants. Future research should focus on comparative assessments, patient satisfaction, and alternative strategies to optimize policy outcomes.